Embossing Technique between III and II Century BC: Experiments and First Results - Andrea Moretti (EXARC, 2020)
The purpose of this paper is to explain our experience with the process of experimental archaeology, involving the reproduction and field testing of embossed decorations, inspired to archaeological finds. As a re-enactment group focused on Celts and Ligurians of III – II century BC we reproduce items and/or ornaments often crafted using the embossing technique: helmets, jewels, brooches, belt buckles and various appliques.